Anti-TNF-Alpha-Adalimumab Therapy Is Associated with Persistent Improvement of Endothelial Function without Progression of Carotid Intima-Media Wall Thickness in Patients with Rheumatoid Arthritis Refractory to Conventional Therapy - Carlos Gonzalez-Juanatey; Tomas R. Vazquez-Rodriguez; Jose A. Miranda-Filloy; Ines Gomez-Acebo; Ana Testa; Carlos Garcia-Porrua; Amalia Sanchez-Andrade; Javier Llorca; Miguel A. González-Gay (Mediators of Inflammation)
To determine whether treatment with the anti-TNF-alpha blocker adalimumab yields persistent improvement of endothelial function and prevents from morphological progression of subclinical atherosclerosis in patients with rheumatoid arthritis (RA) refractory to conventional therapy, a series of 34 consecutive RA patients, attending hospital outpatient clinics and who were switched from disease modifying antirheumatic drug therapy to anti-TNF-alpha-adalimumab treatment because of severe disease, were assessed by ultrasonography techniques before the onset of adalimumab therapy (at day 0) and then at day 14 and at month 12. Values of flow-mediated endothelium-dependent vasodilatation at day 14 and at month 12 were significantly higher (mean ± standard deviation (SD): 6.1±3.9%; median: 5.7% at day 14, and mean ± SD: 7.4±2.8%; median: 6.9% at month 12) than those obtained at day 0 (mean: 4.5±4.0%; median: 3.6%; P=0.03 and P<0.001, resp.). Endothelium-independent vasodilatation results did not significantly change compared with those obtained at day 0. No significant differences were observed when carotid artery intima-media wall thickness values obtained at month 12 (mean ± SD: 0.69±0.21 mm) were compared with those found at day 0 (0.65±0.16 mm) (P=0.3). In conclusion, anti-TNF-alpha-adalimumab therapy has beneficial effects on the development of the subclinical atherosclerosis disease in RA.